The effects of a 16-week aerobic exercise programme on cognitive function in people living with HIV. Issue 6 (3rd June 2017) - McDermott, Adam; Zaporojan, Lilia; McNamara, Patricia; Doherty, Colin P.; Redmond, Janice; Forde, Cuisle; Gormley, John; Egaña, Mikel; Bergin, Colm
ABSTRACT: High levels of cardiovascular fitness and physical activity are associated with higher levels of cognitive function in people with HIV, thus, they may reduce the risk of developing HIV-associated neurocognitive disorder (HAND). This study aimed to investigate the effects of a 16-week aerobic exercise intervention on cognitive function in people with HIV. Eleven participants living with HIV were recruited into the study. Participants were randomised into either an exercise group ( n  = 5), that completed a 16-week aerobic exercise programme training, 3 times per week (2 supervised sessions and one unsupervised session) or a control group ( n  = 6) that received no intervention. Outcomes measured included cognitive function (Montreal cognitive assessment (MOCA) and the Trail making tests A and B), aerobic fitness (modified Bruce protocol), sleep quality (Pittsburgh sleep quality index; PSQI) and physical activity levels (seven-day accelerometry). At baseline, higher levels of moderate physical activity were positively correlated with higher MOCA scores and levels of aerobic fitness were negatively associated with Trail A scores ( P  = 0.04 and P  = 0.001 respectively). However, exercise training did not induce any significant improvements in cognitive function or aerobic fitness. The overall mean adherence rate to the exercise programme was 60%. In conclusion, in the present study a 16-week aerobic exercise intervention did not affect the cognitive function of participants with HIV. It is likely that longer intervention periods and/or higher adherence rates to exercise might be needed for an aerobic exercise programme to be effective in improving cognitive function in a cohort with no baseline cognitive impairments.